Kabela for Enriching the Contemporary Concept of Choreography at Gorontalo - Riana Diah Sitharesmi; Trubus Semiaji (Transbahasa, 2023)
The Kabela is one of traditional dances of Bolaang Mongondow, which reflects the cultural values of North Sulawesi. Behind the ephemeral form and nature, it is necessary to investigate more deeply the rules and essential values, so that the understanding of the meaning of this dance is completely intact for the Gorontalonese as well as the Bolaang Mongondownese. This research is a starting point for mapping dance styles in eastern Indonesia, through strengthening local cultural values in northern Sulawesi in the construction of contemporary choreographic concepts in Gorontalo. The research integrates the ethnographic techniques with methodical experiments in learning process of a non-traditional choreography for the department of Pendidikan Seni Drama, Tari dan Musik at Universitas Negeri Gorontalo. Ethnographic techniques place field research simultaneously with literature studies, to create a qualitative-phenomenological analysis process that considers emic and ethical data. The choreography process adapts Hawkins' exploration model as a guide for realizing experimental works, which also creates an intersubjective understanding discourse process on the Kabela. The results show the Kabela’s presence as symbols of a noble tradition of the Bolaang Mongondownese as well as its structure. The choreographic concepts then intensify the meaning in the production of imaginative and sensory effects, so that the appreciation towards the dance is active and dynamic. This also shows that, it is by understanding others, that the appreciation of one's own is deepened.